Implementation of Artificial Intelligence Technology in the Employee Selection Process: Challenges and Opportunities - Paroli Paroli (Paspama Institute, 2023)
This research aims to explore the implementation of artificial intelligence (AI) technology in the employee selection process and identify related challenges and opportunities. The use of AI in employee selection is an increasingly relevant topic in this digital era, where organizations are trying to increase efficiency and accuracy in selecting prospective employees who suit the company's needs. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of artificial intelligence (AI) technology in the employee selection process has a positive impact, especially in increasing the efficiency and accuracy of recruitment. The use of AI can automate administrative tasks, speed up CV screening, and provide real-time feedback to applicants. Deep data analysis from AI has also been proven to improve evaluations of candidates' technical skills and cultural fit. However, the research also highlights some challenges, such as potential algorithm bias and the difficulty of measuring soft skills. Therefore, the conclusion emphasizes the need for a holistic approach that combines the advantages of AI with human evaluation to ensure fairness and objectivity in the recruitment process.